THE IMPORTANCE OF DIETARY MANAGEMENT IN ATHEROSCLEROSIS - Malika Khusanovna Tolibjonova (Web of Journals Publishing, 2025)
The article highlights modern approaches to dietary therapy in the management of atherosclerosis. Several studies indicate that atherosclerosis can be influenced through appropriate dietary interventions. The main direction of dietary therapy is aimed at regulating total caloric intake, the proportion of proteins, fats, carbohydrates, and other nutrients that may contribute to the progression of atherosclerosis. In patients with excess body weight, reducing daily caloric intake remains the primary strategy for weight reduction, independent of macronutrient composition.
Keywords: Nutrition, atherosclerosis, diet, cardiovascular diseases